2019
DOI: 10.2319/091718-674.1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of different thermoplastic materials for clear aligners

Abstract: Objectives: To investigate the in vitro cytotoxicity of different thermoplastic materials for clear aligners on human primary gingival fibroblasts (HGFs). Materials and Methods: Four materials for clear aligners were considered in this study: Duran (Scheu-Dental GmbH, Iserlohn, Germany), Biolon (Dreve Dentamid GmbH, Unna, Germany), Zendura (Bay Materials LLC, Fremont, CA, USA), and SmartTrack (Align Technology, San Jose, CA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 20 publications
4
45
1
Order By: Relevance
“…Clear aligner treatment has been introduced in the last decades to satisfy the aesthetic and comfort requirements of adult orthodontic patients. This treatment is based on removable thermoplastic splints covering all the teeth and part of the marginal aspects of the gingiva, which progressively move the teeth into an ideal position [13]. Thanks to the satisfactory mechanical proprieties of these devices and to the valuable progresses of the aligners technology, nowadays this therapy is suitable for the correction of a wide spectrum of malocclusions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Clear aligner treatment has been introduced in the last decades to satisfy the aesthetic and comfort requirements of adult orthodontic patients. This treatment is based on removable thermoplastic splints covering all the teeth and part of the marginal aspects of the gingiva, which progressively move the teeth into an ideal position [13]. Thanks to the satisfactory mechanical proprieties of these devices and to the valuable progresses of the aligners technology, nowadays this therapy is suitable for the correction of a wide spectrum of malocclusions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies of aligner effects on oral cells used eluate settings [13][14][15]. In our recent study, we investigated for the first time the behavior of oral squamous carcinoma cells directly grown on SmartTrack ® aligner material and found no adverse effect on these cells [19].…”
Section: Discussionmentioning
confidence: 86%
“…To depict the effects of aligner material on oral cells, aligner eluates have been studied on multiple cells, including gingival fibroblasts, keratinocytes, and breast cancer cells. These studies reported a relatively weak cytotoxic effect of aligners under in vitro conditions [13][14][15]. Further, a recent meta-analysis reported inconsistency in the current literature concerning safety considerations.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cytotoxicity of human primary gingival fibroblasts of four thermoplastic materials was assessed after 14 days of exposure, namely Duran (Scheu-Dental GmbH, Iserlohn, Germany), Biolon (Dreve Dentamid GmbH, Unna, Germany), Zendura (Bay Materials LLC, Fremont, CA, USA), and SmartTrack (Align Technology, San Jose, CA, USA) [23]. Each material exhibited a slight level of cytotoxicity that was comparable to other dental materials, e.g., miniscrews or bonding materials.…”
Section: Materials For Thermoformed Alignersmentioning
confidence: 99%
“…Technical properties and cytotoxicity parameters of the most used thermoplastic materials and printing resins are summarized in Table 1 [19,23,29,36].…”
Section: Development Of Clear Aligners-3d Printingmentioning
confidence: 99%